POTENSI FLAVONOID PADA EKSTRAK DAUN MORINGA OLEIFERA SEBAGAI ALTERNATIF TERAPI ARTRITIS REUMATOID BERBASIS PENDEKATAN ANTIINFLAMASI - Komang Wahyu Widyasanti Sutama; Gregorius William Thongiratama; Putu Dian Amelya Putri Widarani; Ida Ayu Dewi Wiryanthini (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2022)
ABSTRACT Introduction: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease that causes joints inflammation and the most cases are found in the elderly. However, until now pharmacological therapy for RA treatment is still considered inefficient, expensive, and causes many side effects. Therefore, a new alternative treatment is needed. One of the plants that can be used as an alternative is Moringa oleifera due to its anti-inflammatory properties. Discussion: Moringa oleifera leaf extract with ethanol maceration contains flavonoids (12.16%), mostly in the form of quercetin (6.3%). The role of flavonoids as anti-inflammatory agents in RA is to reduce neutrophil activity in the production of proinflammatory cytokines through inhibition of Nuclear Factor kappa-light-chain-enhancer from Activated B Cells (NF-?B) signaling, inhibition of Matrix Metalloproteinase (MMP) activity, and inhibition of the peroxidase active sites at cyclooxygenase-1 (COX-1), cyclooxygenase-2 (COX-2), and 5-lipoxygenase (5-LOX). Quercetin is effective in treating rheumatoid arthritis by providing anti-inflammatory and analgesic effects. The most effective method to obtained Moringa oleifera leaf extract is by drying method with maceration process in 96% ethanol and packaged in oral capsules. Moringa oleifera extract also has fewer side effects compared to currently available RA treatments. Moringa oleifera extract combined with other drugs as adjuvants, such as methotrexate and indomethacin, can increase the anti-inflammatory curative effect in RA without significant side effects. Conclusion: Moringa oleifera leaf extract has potential in the treatment of rheumatoid arthritis. Keywords: Anti-inflammatory, Flavonoids, Moringa oleifera, Rheumatoid Arthritis